Teachers’ Perceptions and Challenges of Inclusion in Early Childhood Education - Eka Apriliya Ernawati; Fattah Hanurawan; Ika Andrini Farida; Esa Arsyiatul Alfath (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Inclusive education in early childhood settings has become a global priority, yet its implementation remains challenging due to teachers’ varying perceptions of children with special needs. This study examines the perceptions of early childhood teachers and evaluates the barriers and opportunities influencing inclusive practices. A systematic literature review of eight peer-reviewed articles was conducted, and data were synthesized through thematic analysis to identify recurring patterns across the studies. Findings indicate that educators typically express positive attitudes toward inclusion; however, lack of professional training, limited resources, and insufficient institutional support often hinder effective practice. The study concludes that strengthening teacher competence, fostering collaboration with families and specialists, and ensuring systemic support are crucial for sustainable inclusive education.